2017
DOI: 10.1101/227751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental and computational framework for a dynamic protein atlas of human cell division

Abstract: SUMMARYEssential biological functions, such as mitosis, require tight coordination of hundreds of proteins in space and time. Localization, timing of interactions and changes in cellular structure are all crucial to ensure correct assembly, function and regulation of protein complexes1-4. Live cell imaging can reveal protein distributions and dynamics but experimental and theoretical challenges prevented its use to produce quantitative data and a model of mitosis that comprehensively integrates information and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 51 publications
5
49
0
Order By: Relevance
“…5e-f). The timing of chromatin association of cohesin and CTCF is consistent with earlier studies 20,31,32 and with more recent chromatin immunoprecipitation experiments that showed CTCF re-binding at CTCF sites during anaphase-telophase, followed rapidly by cohesin accumulation at those sites 32,40 .…”
Section: Condensin Unloading and Cohesin Loading Occurs During The Ansupporting
confidence: 90%
See 1 more Smart Citation
“…5e-f). The timing of chromatin association of cohesin and CTCF is consistent with earlier studies 20,31,32 and with more recent chromatin immunoprecipitation experiments that showed CTCF re-binding at CTCF sites during anaphase-telophase, followed rapidly by cohesin accumulation at those sites 32,40 .…”
Section: Condensin Unloading and Cohesin Loading Occurs During The Ansupporting
confidence: 90%
“…Previous studies have shown that condensin I loading, already high in metaphase, further increases during anaphase and then rapidly decreases, while condensin II colocalizes with chromatin throughout the cell cycle 30 . Cohesin, mostly dissociated from chromatin during prophase and prometaphase 20,21 , reassociates with chromosomes during telophase and cytokinesis, as does CTCF 20,31,32 .). However, it is not known how these events relate to modulation of chromosome conformation and whether distinct chromosome folding intermediates exist in the pathway towards a fully formed interphase nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, introduction of more SA1 can lead to the establishment of new loops within Mbp-sized domains. This more dominant role for SA1 in loop formation is also supported by the reported lag between SA1 and SA2 association to chromatin after mitosis recorded in HeLa cells, which would suggest that loop extrusion by SA1 might commence earlier (Cai et al 2018).…”
Section: Discussionsupporting
confidence: 52%
“…Epigenetic marks, such as histone variant H2A.Z and H3K4 methylation marks, are maintained at both CTCF sites and TSSs in mitosis. Previous studies found evidence for CTCF binding to mitotic chromosomes using imaging and chromatin fractionation approaches (Cai et al 2018;Liu et al 2017;Burke et al 2005).…”
Section: Discussionmentioning
confidence: 99%